EFFECTS OF LUMBAR SNAG AND MECHANICAL TRACTION IN PATIENTS WITH DISCOGENIC LUMBOSACRAL RADICULOPATHY - Muzammal Ahmed; Naveed Anwar; Sana Tauqeer; Kehkhshan Khalid; Hammad Shakeel (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the effects of lumbar sustained natural apophyseal glide and Mechanical Traction in patients with discogenic lumbosacral radiculopathy.